Telemedicine technology acceptance - survey research among hospitalized and ambulatory patients in Poland - Kmiotek, Patrycja; Materniak, Andrzej; Inglot, Anna; Majchrowska, Anita; Nowakowska, Luiza (Journal of Education, Health and Sport, 2019)
Introduction.Telemedicine can be defined as the use of telecommunication technologies to provide medical information and services. Telecare includes devices which are capable of monitoring vital signs and contact the doctor remotely. In the case of a sudden health problems it is possible to quickly localize patient through built-in GPS.Aim of the study.Evaluation of social awareness in the field of telemedicine and patients’ willingness to use modern technologies for indirect contact with a physician.Material and method.Survey research carried out among hospitalized and ambulatory patients.Results.The questionnaire was returned by 198 patients. Only 24.5% of hospitalized and 18.6% ambulatory patients stated that the concept of telemedicine is known to them. 56.1% of respondents declared their willingness to remotely consult a doctor. The greatest interest was expressed by people aged 18-30 - 74.1% of respondents compared to 50.7% among patients over 60 years. The interest of remote consultation was comparable between city dwellers and inhabitants of rural areas (59.3 % compared to 54.12%).Conclusions.The results of our study show that public awareness in field of telemedicine is small. Without increasing information policy about possibility of using a remote form of contact with physician among patients, potential of telemedicine will remain unused. High interest in teleconsultation among young patients gives hope for a wide application in the future.